Anthracene-based blue fluorescence materials utilized in non-doped OLEDs with high luminance and a low efficiency roll-off. (August 2022) - Zhao, Zhenhong; Wang, Guoliang; Luo, Xin; Tian, Xiangbin; Zhang, Daqing; Guo, Shiyan; Zhou, Haitao; Miao, Yanqin; Huang, Jinhai; Wang, Hua
Abstract: In this work, we designed and synthesized two novel blue-emitting compounds ( m -TAC and p -TAC ) with a twisted D-π-A configuration by incorporation of 2, 4, 6-triphenyl-1, 3, 5-triazine as an acceptor and carbazole as a donor through an anthracene π-spacer. Therein, p -TAC exhibits a hybridized local and charge-transfer (HLCT) characteristic with a sky-blue emission at 462 nm in toluene while m -TAC shows emission maximum at 431 nm. The two compounds exhibit superb thermal stability in the company of a thermal decomposition temperature ( T d ) as high as 507 and 516 °C. It is noticed that the non-doped devices with m -TAC and p -TAC as blue emitters display a turn-on voltage ( V on ) of 3.2 V and achieve sky-blue emission at 460 and 476 nm. In particular, the optimized device based on p -TAC realizes a maximum luminance above 10 000 cd m −2 and the maximum external quantum efficiency ( EQE max ) reaching 5.03%. As a sky-blue HLCT emitter, p -TAC reveals high-efficiency electroluminescence (EL) performance, providing a new insight for further industrial applications. Graphical abstract: A new blue fluorescent material based on anthracene was synthesized. The non-doped devices were fabricated with a maximum luminance of 13 630 cd m −2, maximum external quantum efficiency reaching 5.03% and a negligible efficiency roll-off of 1.4% at 1000 cd m −2 . Image 1 Highlights: Two materials ( m -TAC and p -TAC ) based on anthracene for sky-blue OLEDs was presented. p -TAC possesses HLCT characteristic, excellent thermal stability and sky-blue emission. Non-doped device based on p -TAC exhibits Lmax of 13630 cd m −2, EQE max of 5.03% and low roll-off of 1.4% at 1000 cd m −2 .